2003
DOI: 10.4049/jimmunol.170.12.6082
|View full text |Cite
|
Sign up to set email alerts
|

Functional Epitope on Human Neutrophil Flavocytochrome b558

Abstract: mAb NL7 was raised against purified flavocytochrome b558, important in host defense and inflammation. NL7 recognized the gp91phox flavocytochrome b558 subunit by immunoblot and bound to permeabilized neutrophils and neutrophil membranes. Epitope mapping by phage display analysis indicated that NL7 binds the 498EKDVITGLK506 region of gp91phox. In a cell-free assay, NL7 inhibited in vitro activation of the NADPH oxidase in a concentration-dependent manner, and had marginal effects on the oxidase substrate Michae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…3, curve c), the gp91 phox -specific mAb NL7 (data not shown), or an irrelevant, anti-rhodopsin mAb K16 (data not shown). Similar to mAb 44.1, mAbs 54.1 and NL7 recognize the cytoplasmic surface of Cyt b (31,33) and have been shown to efficiently bind detergent-solubilized Cyt b by fluorescence resonance energy transfer under these experimental conditions (R. M. Taylor and A. J. Jesaitis, unpublished data). Additional control experiments demonstrated that preincubation of DDM-solubilized Cyt b with unlabeled mAb 44.1 does not interfere with the binding of CCB-mAb 54.1 (data not shown).…”
Section: Resonance Energy Transfer Studies Investigating the Assignmementioning
confidence: 91%
See 3 more Smart Citations
“…3, curve c), the gp91 phox -specific mAb NL7 (data not shown), or an irrelevant, anti-rhodopsin mAb K16 (data not shown). Similar to mAb 44.1, mAbs 54.1 and NL7 recognize the cytoplasmic surface of Cyt b (31,33) and have been shown to efficiently bind detergent-solubilized Cyt b by fluorescence resonance energy transfer under these experimental conditions (R. M. Taylor and A. J. Jesaitis, unpublished data). Additional control experiments demonstrated that preincubation of DDM-solubilized Cyt b with unlabeled mAb 44.1 does not interfere with the binding of CCB-mAb 54.1 (data not shown).…”
Section: Resonance Energy Transfer Studies Investigating the Assignmementioning
confidence: 91%
“…FACS analysis evaluating the binding of mAbs to intact human neutrophils was conducted as previously described (31).…”
Section: Elisa Western Blotting and Facs Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…DMF-differentiated PLB cells are a well-characterized model of PMN that have been extensively used for studies of biochemical activation and functional responses (e.g., respiratory burst, granule exocytosis) (55,56,73,74). Incubation of differentiated PLB cells in FN-coated wells was associated with rapid and sustained production of PA and PEt (Fig.…”
Section: Pld Activity Is Increased During Adhesion Of Primary Human Nmentioning
confidence: 99%